Statin Use, Ageing, and Cognition: A Review. (June 2016) - Stephenson, Nadine E; Crowe, Simon F
Abstract : Cholesterol performs a number of important roles in normal brain functioning, including the formation of myelin sheaths and communication between cells, and it has been theorised that statin use could disrupt these roles leading to deficits in cognition. Relevant research was identified via the La Trobe University library Summon TM search tool, using search terms including "statin cognition, " "statins cognition, " "statin brain, " "cholesterol cognition, " "cholesterol brain, " and "statin adverse effects" in addition to examination of the reference lists of the retrieved research articles. Research was examined from the published literature across several different research modalities: systematic reviews and meta‐analyses, randomised control trials, cohort studies, and case reports. On the basis of the surveyed literature, it is not possible to indicate any consistent caution or limitation with regard to the use of statins and their effects upon cognitive functioning due to the contradictory and inconsistent results arising from this literature. In summary, it is not possible to conclusively determine whether there are either cognitive benefits or detriments associated with the use of the statins. The determination of the effect of these agents on neuropsychological functioning requires more methodologically controlled long‐term longitudinal follow‐up studies of these treatments due to the complex and multisystem effects of these agents.